Exploration of Mathematical Values on Traditional Umbrellas in the Alas Indigenous Community in Southeast Aceh - Dinda Dinda; Machrani Adi Putri Siregar (MASI Mandiri Edukasi, 2025)
This study explores ethnomathematics embedded in the forms and motifs of the Payung Mesikhat, a cultural symbol of the Alas Indigenous community in Darul Amin Village, Southeast Aceh Regency. A qualitative approach with an ethnographic method was employed to uncover the mathematical meanings inherent in the geometric elements of this traditional umbrella. Data were collected through observation, in-depth interviews with cultural figures and artisans, and visual documentation. To analyze the geometric shapes identified, GeoGebra was used as a tool for visualization and mathematical representation. The findings reveal that the Payung Mesikhat embodies various mathematical concepts, such as reflection symmetry, rotation, geometric transformations, patterns, and repetitions, each carrying philosophical significance in the Alas culture. With the aid of GeoGebra, these concepts can be represented visually and interactively, thereby supporting contextual mathematics learning based on local culture. This study is expected to enrich locally grounded mathematics teaching materials and strengthen cultural preservation through educational approaches.